1997
DOI: 10.1007/bf01808823
|View full text |Cite
|
Sign up to set email alerts
|

EBIC-Guidelines for management of severe head injury in adults

Abstract: SummaryGuidelines for the management of severe head injury in adults as evolved by the European Brain Injury Consortium are presented and discussed. The importance of preventing and treating secondary insults is emphasized and the principles on which treatment is based are reviewed. Guidelines presented are of a pragmatic nature, based on consensus and expert opinion, covering the treatment from accident site to intensive care unit. Specific aspects pertaining to the conduct of clinical trials in head injury a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
232
0
17

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(252 citation statements)
references
References 26 publications
3
232
0
17
Order By: Relevance
“…In contrast, brain tissue hypoxia (, 20 mm Hg) is associated with poor outcomes in the severely injured brain and oxygendirected strategies may improve outcomes (27,56,57). Although the optimal strategy to restore brain tissue oxygen tension to normal levels after brain injury is unknown, guidelines recommend targeting oxygenation values toward or within normal limits (58,59). In practice, based on the observation that brain tissue oxygen tension appears to be highly dependent on diffusion of dissolved oxygen (60), a common, albeit controversial, strategy in treating patients with traumatic brain injury is to use high FI O2 to achieve supraphysiological Pa O2 values to restore brain tissue oxygen levels (57).…”
Section: Perspectivesmentioning
confidence: 99%
“…In contrast, brain tissue hypoxia (, 20 mm Hg) is associated with poor outcomes in the severely injured brain and oxygendirected strategies may improve outcomes (27,56,57). Although the optimal strategy to restore brain tissue oxygen tension to normal levels after brain injury is unknown, guidelines recommend targeting oxygenation values toward or within normal limits (58,59). In practice, based on the observation that brain tissue oxygen tension appears to be highly dependent on diffusion of dissolved oxygen (60), a common, albeit controversial, strategy in treating patients with traumatic brain injury is to use high FI O2 to achieve supraphysiological Pa O2 values to restore brain tissue oxygen levels (57).…”
Section: Perspectivesmentioning
confidence: 99%
“…13 The question may be raised as to whether an intracranial blood volume-reducing therapy induced by hypothermia would be as effective as the established ICP-reducing therapies, which mainly act by reducing brain oedema. [24][25][26][27] Ongoing studies…”
Section: Can Alternative Protocols Improve Outcome?mentioning
confidence: 99%
“…18 The use of vasoconstrictors is an important component to counteract hypothermia-induced reduction in arterial pressure in the ongoing study by Clifton et al 29 Even though the use of vasoconstrictors is common in the treatment of TBI patients and favoured in traditional guidelines to increase cerebral perfusion pressure, 24,25 serious concerns have been raised since almost two decades in the use of these drugs in TBI patients, as they may compromise the circulation further of the hypoxic penumbra zone. 26,27 A recent study even showed that cerebral oxygenation was negatively affected by an infusion of norepinephrine in healthy subjects.…”
Section: Hypothermia-induced Use Of Vasoconstrictorsmentioning
confidence: 99%
“…[1,4,5]. Основным механизмом дей-ствия декомпрессии является создание дополни-тельного пространства для компенсации увеличен-ного внутричерепного объема [6][7][8]11]. Считается, что эффективность декомпрессии зависит от разме-ра декомпрессионного окна [9][10][11].…”
unclassified